THE ROLE OF INDONESIAN MIGRANT WORKERS IN EXPORT POTENTIAL PONOROGO REVIEWED BY ISLAMIC ECONOMICS - Nurhayati, Ani; Syakarna, Nugraheni Fitroh R.; Albanjari, Fatkhur Rohman (Jurnal Syarikah : Jurnal Ekonomi Islam, 2024)
This study aims to determine the role of Indonesian migrant workers in export potential Ponorogo in terms of Islamic economics. The research design used is descriptive qualitative research with a library research approach. The population in this study is all data on Indonesian Migrant Workers and Exports, with the research samples are data on Indonesian Migrant Workers and Commodities Ponorogo Regency that have the potential to be exported. The type of data used in this study is secondary data of time series data 2019 to 2023. The data collection technique uses a library research approach sourced Indonesian Migrant Workers Protection Agency, Statistics Agency, Population and Civil Registration Office, Manpower Office, Industry, Trade, Cooperatives, and Micro Units Office of Ponorogo Regency, and some previous research related to the topic. The data analysis technique uses descriptive analysis, where the data obtained from library research is entered into a table and then described using sentences that describe the actual situation. The research results show that the role of Indonesian migrant workers in export potential Ponorogo are in line with the principle of Al-Adl wa Al-Ihsan. In Islamic Economics, export activities and working abroad as Indonesian migrant workers, is contained in QS. Al-Mulk: 15.